Safety and efficacy of catheter directed thrombolysis (CDT) in elderly with pulmonary embolism (PE). Issue 1 (24th March 2021) - Harrison, Eneida; Kim, Jin Sun; Lakhter, Vladimir; Lio, Ka U; Alashram, Rami; Zhao, Huaqing; Gupta, Rohit; Patel, Maulin; Harrison, James; Panaro, Joseph; Mohrien, Kerry; Bashir, Riyaz; et al.
Abstract : Introduction: Acute pulmonary embolism (PE) remains a common cause for morbidity and mortality in patients over 65 years. Given the increased risk of bleeding in the elderly population with the use of systemic thrombolysis, catheter-directed therapy (CDT) is being increasingly used for the treatment of submassive PE. Nevertheless, the safety of CDT in the elderly population is not well studied. We, therefore, aimed to evaluate the safety of CDT in our elderly patients. Methods: We conducted a retrospective observational study of consecutive patients aged > 65 years with a diagnosis of PE from our Pulmonary Embolism Response Team database. We compared the treatment outcomes of CDT versus anticoagulation (AC) in elderly. Propensity score matching was used to construct two matched cohorts for final outcomes analysis. Results: Of 346 patients with acute PE, 138 were > 65 years, and of these, 18 were treated with CDT. Unmatched comparison between CDT and AC cohorts demonstrated similar in-hospital mortality (11.1% vs 5.6%, p=0.37) and length of stay (LOS) (3.81 vs 5.02 days, p=0.5395), respectively. The results from the propensity-matched cohort mirrored results of the unmatched cohort with no significant difference between CDT and AC in-hospital mortality (11.8% vs 5.9%, p=0.545) or median LOS (3.76 vs 4.21 days, p=0.77), respectively. Conclusion: In this observational study using propensity score-matched analysis, we found that patients >65 years who were treated with CDT for management of acute PE had similar mortality and LOS compared with those treated with AC. Further studies are required to confirm these findings.